Računalništvo in informatika v logistiki - Gumzej, Roman (University of Maribor Press, 2024)
Computing and Informatics in Logistics. This textbook is predominantly meant for first year students at the Faculty of Logistics. It represents the primary source of information for the subjects Fundamentals of Computer Science at the bachelors and Computer Science and Informatics in Logistics at the university study programme. By these courses the fundamentals of computer-based logistics information systems are set. Here, their purpose, role and tasks as well as their components are presented, namely their dataware, hardware, netware, software and orgware. Within their tutorials the focus is on computer-aided engineering of logistics information systems at the university and business analytics and decision support systems at the bachelors study programme, respectively. Their contents are rounded up with the presentation of the methods and mechanisms of safety and security in computer based logistics information systems. This textbook lays the foundations for subsequent specialised courses on Business information systems, Information Support in Logistics Information Systems and Processes as well as Logistics Information Systems Integrations.